Spider-Man. Far from home [videorecording (Blu-Ray)] - Holland, Tom, 1996-; Jackson, Samuel L.; Zendaya, 1996-; Smulders, Cobie, 1982-; Favreau, Jon; Tomei, Marisa; Gyllenhaal, Jake, 1980- (Sony Pictures Home Entertainment, 2019)
Peter Parker returns for the next chapter of the Spider-Man: Homecoming series! Our friendly neighborhood Super Hero decides to join his best friends Ned, MJ, and the rest of the gang on a European vacation. However, Peter's plan to leave super heroics behind for a few weeks are quickly scrapped when he begrudgingly agrees to help Nick Fury uncover the mystery of several elemental creature attacks, creating havoc across the continent!